Prevalence of Pes Planus and Pes Cavus in School Going Children: Foot Arch Disorders Prevalence - Qasim, Muhammad; Rauf, Wardah; Toqueer, Sana; Ahmed, Taimoor; Sukhera, Sadia; Wamiq, Alishba (THE THERAPIST (Journal of Therapies & Rehabilitation Sciences), 2024)
Pes planus and pes cavus are common foot deformities that may affect a child’s posture and mobility. Objective: To investigate the incidence of idiopathic pes planus and pes cavus among school-going children with no known neurological or anatomical irregularities and without any known systemic diseases. Methods: This descriptive cross-sectional study was conducted on 75 school-going children aged 5 to 12 years in Lahore, using a convenient sampling technique. Data were collected through structured footprint analysis and a demographic questionnaire. Footprints were obtained using the ink method and analyzed using Staheli’s Index to classify foot types as normal, pes planus, or pes cavus. Children with neurological disorders, foot deformities, systemic diseases, or a history of lower limb surgeries were excluded. Data were collected using SPSS version 26.0. Results: A total of 75 school-going children participated in the study, with a mean age of 9.35 ± 1.90 years. About half of the participants (52%) reported engaging in physical activity. Sandals were the most commonly worn footwear (34.7%), followed by barefoot walking (24%). A positive family history of foot conditions was reported by 56%, and 46.7% experienced foot pain. Foot type analysis showed that the majority had normal arches (64% both feet), with pes cavus more prevalent on the right foot (33.3%) than pes planus (2.7%). On the left foot, pes cavus and pes planus were observed in 25.3% and 10.7%, respectively. Conclusion: Pes cavus was more prevalent than pes planus, especially in the right foot, though overall rates were low.